Impact of Income Tax Exemption on BPKH’s Financial Performance in Hajj Fund Management (2018–2023) - Alvira Sya’bannia Putri; Agus Puji Priyono (Akuntansi: Jurnal Akuntansi Integratif, 2025)
This study examines the impact of the income tax (PPh) exemption policy on the financial performance of the Hajj Financial Management Agency (BPKH). Regulated under Law No. 11 of 2020 and Minister of Finance Regulation (PMK) No. 18 of 2021, this policy aims to optimize Hajj fund management. Using fiscal policy and stewardship theory, the study compares BPKH’s financial performance before (2018–2019) and after (2022–2023) the policy implementation through financial ratio analysis, including solvency, efficiency, and profitability ratios. A quantitative approach was employed with descriptive statistics and the Wilcoxon signed-rank test. Results indicate that while changes were observed in financial ratios, they were not statistically significant. However, a positive shift in investment composition was noted, with a higher allocation to return-generating instruments post-policy. This suggests an improvement in BPKH’s investment strategy, even though its impact on financial ratios remains statistically insignificant. These findings highlight the need for further evaluation of tax incentives in enhancing the financial sustainability of Hajj fund management